Determinants of working until retirement compared to a transition to early retirement among older workers with and without chronic diseases: Results from a Dutch prospective cohort study. Issue 3 (May 2018) - Sewdas, Ranu; van der Beek, Allard J.; de Wind, Astrid; van der Zwaan, Lennart G.L.; Boot, Cécile R.L.
Aim: The ageing society and recent policy changes may lead to an increase of older workers with chronic diseases in the workforce. To date, it is unclear whether workers with chronic diseases have specific needs while employed. The aim of this study is to explore the differences in determinants of working until retirement compared to a reference group who have transitioned to early retirement among workers with and without chronic diseases. Methods: Dutch workers aged 57–62 years ( n = 2445) were selected from an existing prospective cohort study, 'STREAM'. The potential determinants were categorized into: individual, health, work-related and social factors. Logistic regression analyses were performed to determine the associations between these determinants and working until retirement – once for workers with and once for those without chronic diseases. To test differences, we included an interaction term between the determinant and the covariate 'having a chronic disease yes/no' in the analyses of the total population. Results: In total, 1652 (68%) persons were employed from 2011 to 2013. The majority of the determinants appeared to be similar for workers with or without a chronic disease; the interaction terms for these determinants and the covariate 'having a chronic disease' showed a p -value higher than 0.05, except for one individual factor (i.e. mastery) and one work-related factor (i.e. autonomy), which showed a p -value below 0.05. Higher mastery and higher autonomy were statistically significantly associated with working until retirement for those with chronic diseases, whereas they were not for those without chronic diseases. Conclusions: Differences between workers with and without chronic diseases may exist for working until a statutory retirement age. Interventions aimed at encouraging work participation of older workers should make a distinction between the two groups. Autonomy at work and mastery were found to be factors that may promote work participation until higher age, specifically for older workers with chronic diseases.